Microstructural and morphological analysis of pure and Ce-doped tin dioxide nanoparticles - Maciel, A. P.; Lisboa Filho, Paulo Noronha [UNESP]; Leite, E. R.; Paiva-Santos, C. O.; Schreiner, W. H.; Maniette, Y.; Longo, Elson [UNESP] (Elsevier B.V., 2003)
Structural morphological studies in pure and Ce-doped tin dioxide nanoparticles with high stability against particle growth were performed in samples, obtained using the polymeric precursor method and prepared at different annealing temperatures. A Ce-rich surface layer was used to control the particle size and stabilize SnO2 against particle growth. The formation of this segregated layer can contribute to a decreased surface energy, acting in the driving force, or reducing the surface mobility. Only the cassiterite SnO2 phase was observed below 1000 degreesC and a secondary phase (CeO2) was observed for the Ce-doped SnO2 at temperatures higher than 1000 degreesC, when de-mixing process occurs. The evolution of crystallite size, microstrain and morphology of the nanoparticles with annealing temperatures was investigated by X-ray diffraction (XRD), associated to Rietveld refinements, X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: SnO2; powders-chemical preparation; X-ray methods; precursors-organic